Lista dos Lepidópteros (Insecta) da ilha do Pico (Açores) - Vieira, Virgílio (1992)
A list of butterflies and moths collected by the authors at Pico, island of the Azores Archipelago, in 1992 is presented. From that list and the published literature a preliminary survey of the Lepidoptera of the Pico island is elaborated. This survey contains 69 species or subspecies, of which, four are new records for Pico island.